Flight test as a criterion for evaluating the quality of Telenomus podisi (Hymenoptera: Scelionidae) (Research, Society and Development, 2023)
Egg parasitoids are considered natural enemies used in the management of bed bugs, since they eliminate the pest even before damage occurs. For the parasitoid to perform its control function under field conditions, the ability to fly and walk are characteristics that must be monitored, as they are related to foraging and dispersal in the field. Thus, the objective of this work was to evaluate the flight quality of the population of Telenomus podisi, reared on eggs of the stink bug Diceraeus melacanthus, under laboratory conditions. The experiment was carried out in a laboratory in a climate-controlled chamber with a temperature of 25°C±1°C, a photoperiod of 12 hours and a relative humidity of 60%±10%. The design used was completely randomized with three treatments (parasitoid-host ratios: 1:1, 3:1 and 4:1) and five repetitions, each mass with 20 eggs of Diceraeus melacanthus being considered a repetition. The parameters evaluated in the research were the flight capacity of flying, non-flying and walking parasitoids through a test unit similar to the ESALQ model. Data were compared using Tukey's test (p